A Literature Review Of Nanocarrier Development Through Emulsification Diffusion Method (Edm) - arafat, Md yeasin; Nijhu, Rajia Sultana (Indonesian Journal of Pharmaceutics, 2024)
An overview of the development of nanocarriers is presented in this work using the practical technique of the Emulsification Diffusion Method (EDM). The field of nanomedicine, which combines nanotechnology and medicine, involves creating new therapeutic and diagnostic modalities by employing precisely designed substances with this range of lengths. Many medicinal products and diagnostic tools based on nanoparticles have been developed. The emulsification-diffusion method (EDM) was utilized to prepare nanometer-sized particles, which are commonly used as polymeric carriers. The process involves emulsifying a drug and polymer solution in an aqueous phase that has been saturated with stabilizers and then adding an excessive amount of water.  Investigations into how process variables affect the average size of nanoparticles have been carried out. It was made apparent that the kind and concentrations of stabilizer, the speed at which the magnetic stirrer homogenizes, and the polymer concentration all affected the size of the nanoparticles. Additionally, the medications integrated into nanocarriers have a longer half-life in circulation, which boosts their effectiveness and allows for a lower application dose. Because of their small size and high surface area, drug nanocarriers are also more bioavailable and soluble, which allows their many atoms and high surface energy to act as catalysts. Keywords: Nanocarrier,Diffusion,Bioavailability,Solubility,Catalysts.